PALLIATIVE STENTING FOR MALIGNANT GASTRO-DUODENAL OBSTRUCTION–A DISTRICT GENERAL HOSPITAL EXPERIENCE. (8th June 2013) - Trotter, M; Balamurugan, R; Dear, K; Naylor, G; Everitt, N; Ravi, K
Abstract : Introduction: For 5 years we have run a combined endoscopic and radiological service to treat malignant gastric outlet obstruction with stenting. In an age of centralization of services for upper GI malignancies we have looked at our outcomes from this service. Aims/Background: To assess the outcomes of palliative stenting for malignant gastro-duodenal obstruction against published data. Method: All patients who underwent palliative stenting for malignant gastro-duodenal tumours in our centre from 2007 up to January 2013 were retrospectively analyzed. Two patients were excluded due to non-availability of notes. Outcomes were assessed for technical and clinical success, return to oral nutrition, complication and re-intervention rates and overall survival. Results: 32 stents were placed in 29 patients. The service was provided by the same radiologist in 94% of cases and by the same two endoscopists in 79% of cases. Technical success was 100% and clinical success and return to oral nutrition was 91%. Complication rate was 16% (2 stents migrations, one tumour overgrowth and two patients had food bolus obstruction). Re-intervention rate was 13% with 3 re-stenting procedures and 1 gastroenterostomy. Mean survival was 91 days (5–392). Median wait from decision to stent to actual stenting was 1 day, (0–14). Overall 25 covered and 9 uncovered stents were inserted. Conclusion: Stenting for gastric outlet obstruction in this patient group is an established preferable alternative to surgical intervention. Much of the treatment for upper GI malignancies have now been centralized. Our data shows comparable results with other published data for these procedures with a high success rate and low major complication rates. It is of considerable benefit to these patients not to have to travel to a regional centre for stenting.